Analisis Manajemen Risiko Terkait Regulasi Perjalanan Umrah di AET Travel - Yeni, Putri Halida; Ridhah, Habibatur (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Established on October 21, 2010, AET Travel is a hajj and umrah travel company that offers the best packages and services with the highest level of service. The dangers associated with the rules will not be separated from the name of the hajj and umrah company. Therefore, to prevent and reduce the dangers that arise, AET Travel must carry out risk management related to the requirements of the umrah trip. The purpose of this study is to determine how the leaders of AET Travel manage and overcome risks related to the analysis of organizational risk management against the law of umrah travel. Using a qualitative approach, this study collected data through field observations and interviews with key informants, especially the leaders of AET Travel. Interviews with informants were then documented using photos. According to the research findings, issues of security, health, and regulation are issues that often arise. Then, by identifying risks, namely by recognizing and understanding the dangers that will arise, AET Travel has succeeded in implementing risk management. After that, a risk analysis is carried out, namely finding out what will happen if the risk is ignored. Then make an assessment by implementing the selected approach, especially, risk reduction strategies in practice.